A professional development assessment guide preparation and validation at the Public Health National School - Esther Paredes Esponda; Liliam Quelle Santana; María Luisa Quintana Galende; Indira Barcos Pina; Inarvis Medina González; Yadimir Martínez Blanco (Medisur)
Foundation: the professional development process at the Public Health National School has channeled a project towards quality management that includes evaluation as a principle to achieve it; therefore, an instrument that allows evaluating quality in the process is necessary. Objective: to validate the professional development assessment guide. Methods: a research was carried out in Health Policies and Systems, at the Public Health National School, Havana, from January 2023 to February 2024, which classifies as a technological development work type Research + Development + Innovation (R+D+I), for the development and validation of an instrument that measures the professional development process quality in this institution. The unbiased and corrected total content validity coefficient, by Hernández Nieto, was calculated, with a confidence level of 95.0%. The same measures each instruments content validity, according to the expert judgment technique. Results: A guide for the professional development programs quality evaluation was obtained and it was proven that the designed instrument meets the appearance validity requirements and content according to the obtained indicators. Conclusions: the developed guide will allow a thorough evaluation of the professional development process at the Public Health National School.